Aspects of Grammatical Cohesion in Legal Texts: A Case Study of the Penal Code of the United Arab Emirates - Alzaabi, Shaikha; Alaoui , Hafid (Al-Adab Journal, 2025)
This research aims to highlight the features of syntactic cohesion in legal texts, using the Penal Code of the United Arab Emirates (Law of Crimes and Punishments) as a practical example for study. We focused on uncovering the manifestations of syntactic cohesion in this study by examining the structural relationships between sentences and the consistency that binds them together, demonstrating the legal text's coherence at the structural level. The sentences in the text are composed of a collection of words that guide us to the legal meaning, with the purpose of these words not being their individual meanings, but rather their organization, so they interconnect and interact to convey a unified semantic meaning, which is the fundamental purpose of legislation. Through this study, we will attempt to explore the significance of structural relationships in achieving overall cohesion in the legal texts (articles) of the corpus, such as predicative linking, additive linking, conditional linking, and referential linking.